2012
DOI: 10.1210/jc.2011-3115
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Ectopic Location of a Parathyroid Carcinoma Arising within the Thyroid Gland

Abstract: Introduction: Parathyroid carcinomas are very rare tumors and may arise in the normally located or ectopic gland. The latter present certain diagnostic difficulties, and there are no specific guidelines on their management. We present a case of parathyroid carcinoma arising within an ectopically located intrathyroid gland and discuss the diagnosis, management, and difficulties encountered. Furthermore, we review all six previously reported cases of this rare event and demonstrate the patterns in presentation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 19 publications
0
11
0
4
Order By: Relevance
“…The radioisotope is taken up by the diseased parathyroid rapidly and retained longer [2]. However, some patients with PC may have negative scans [39].…”
Section: Localizing Examination Of Parathyroid Cancermentioning
confidence: 99%
See 4 more Smart Citations
“…The radioisotope is taken up by the diseased parathyroid rapidly and retained longer [2]. However, some patients with PC may have negative scans [39].…”
Section: Localizing Examination Of Parathyroid Cancermentioning
confidence: 99%
“…It has been reported that sensitivity for FNA in diagnosing malignancy is about 50% [2]. In 1973 Schantz and Castleman proposed the criteria that may be helpful to diagnose cancer.…”
Section: Histopathological Examinationmentioning
confidence: 99%
See 3 more Smart Citations